The impact of anchor stores on the performance of shopping centres: the case of Sonae Sierra - Damian, D. S.; Curto, J. D.; Pinto, J. C. (International Journal of Retail & Distribution Management, 2011)
Purpose: The purpose of this paper is to determine the impact of anchor stores on the performance and results of shopping centres and on the prices practiced by other stores. It analyses the customer spill-over effect of the anchor stores on the Sonae Sierra shopping centres. Incorporated in Portugal in 1989, Sonae Sierra is an international corporation specializing in shopping centres. It is co-owned by Sonae (Portugal) and Grosvenor (UK) who each own 50 per cent. Design/methodology/approach: The data collection targeted 35 shopping centres in Portugal and Spain with 1,200,000 square feet (or more), for three consecutive years (2005-2007). The anchor stores provide about 41 per cent of the total gross lettable area and on average pay only 18 per cent of the total rent collected by the developer. The ordinary least squares and Kruskal-Wallis statistic (in order to avoid ANOVA assumption violations) are used to test the hypotheses. Findings: The empirical analysis shows that a greater presence of anchors in a mall directly increases the sales, and consequently the rents of non-anchor stores in a mall. The authors demonstrate that externalities are internalized by efficient allocation of space and incentives across stores, and also show that the anchor stores increased the malls' customer drawing power, measured as the number of people who visited the mall at a given time, although lately they have had less impact on the sales per person visiting the centres. Research limitations/implications: This study is limited in that it surveyed only Sonae Sierra shopping centres, hence the results can only be generalized using this model as a basis. Other limitations were an inability to gather data on customer purchasing power in the areas surrounding the Sonae Sierra shopping centres, and the need to safeguard the confidentiality of the information, which did not allow the use of more independent variables for the models. Practical implications: It is demonstrated that the total sales of the shopping malls are directly influenced by the number of anchors, and that the area allocated to them is a strategic tool. Originality/value: The paper uses unique data consisting of mall store contracts to study the complex economic issues that arise when stores co-occupy a large shopping centre.